A Composite of Functional Status and Pneumonia Severity Index Improves the Prediction of Pneumonia Mortality in Older Patients - Sanz, Francisco (J Gen Intern Med, 2018)
BACKGROUND: The baseline health status may be a determinant of interest in the evolution of pneumonia. OBJECTIVE: Our objective was to assess the predictive ability of community-acquired pneumonia (CAP) mortality by combining the Barthel Index (BI) and Pneumonia Severity Index (PSI) in patients aged ≥ 65 years. DESIGN, PATIENTS AND MAIN MEASURES: In this prospective, observational, multicenter analysis of comorbidities, the clinical data, additional examinations and severity of CAP were measured by the PSI and functional status by the BI. Two multivariable models were generated: Model 1 including the PSI and BI and model 2 with PSI plus BI stratified categorically. KEY RESULTS: The total population was 1919 patients, of whom 61% had severe pneumonia (PSI IV–V) and 40.4% had some degree of dependence (BI ≤ 90 points). Mortality in the PSI V–IV group was 12.5%. Some degree of dependence was associated with increased mortality in both the mild (7.2% vs. 3.2%; p = 0.016) and severe (14% vs. 3.3%; p < 0.001) pneumonia groups. The combination of PSI IV–V and BI ≤ 90 was the greatest risk factor for mortality (aOR 4.17; 95% CI 2.48 to 7.02) in our series. CONCLUSIONS: The use of a bimodal model to assess CAP mortality (PSI + BI) provides more accurate prognostic information than the use of each index separately.